2021
DOI: 10.1186/s12862-021-01920-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between sympatric and allopatric Coregonus ciscoes in North and Central Europe

Abstract: Background Sympatric speciation along ecological gradients has been studied repeatedly, in particular in freshwater fishes. Rapid post-glacial ecological divergence has resulted in numerous endemic species or ecologically distinct populations in lakes of the temperate zones. Here, we focus on the Baltic cisco (Coregonus albula) complex, to study the genetic similarity among two pairs of sympatric autumn- and spring-spawning populations from post-glacial German Lakes Stechlin and Breiter Luzin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Angienda et al ( 2011 ) reported a relatively high genetic diversity for Oreochromis esculentus ( H O = 0.795–0.81, H S = 0.745–0.77, Ᾱ R = 7.13–8.13) and Oreochromis niloticus ( H O = 0.70–0.78, H S = 0.71–0.79, Ᾱ R = 7–8.38) populations in eastern Africa. Mehner et al ( 2021 ) found high genetic diversity in the European Coregonus cisco populations ( A R = 3.4–6.3). Many studies on the genetic diversity of other species from the Channidae family such as Channa striata (Adamson et al, 2012 ; Robert et al, 2019 ; Tan et al, 2016 ) and Channa marulia (Pathak et al, 2018 ) showed relatively high genetic diversity.…”
Section: Discussionmentioning
confidence: 98%
“…Angienda et al ( 2011 ) reported a relatively high genetic diversity for Oreochromis esculentus ( H O = 0.795–0.81, H S = 0.745–0.77, Ᾱ R = 7.13–8.13) and Oreochromis niloticus ( H O = 0.70–0.78, H S = 0.71–0.79, Ᾱ R = 7–8.38) populations in eastern Africa. Mehner et al ( 2021 ) found high genetic diversity in the European Coregonus cisco populations ( A R = 3.4–6.3). Many studies on the genetic diversity of other species from the Channidae family such as Channa striata (Adamson et al, 2012 ; Robert et al, 2019 ; Tan et al, 2016 ) and Channa marulia (Pathak et al, 2018 ) showed relatively high genetic diversity.…”
Section: Discussionmentioning
confidence: 98%
“…However, significant genetic differences between fish from between them. Interestingly, another species in the C. albula species complex (Mehner et al, 2021;Sendek et al, 2013;Sendek, 2021; Table 1), the closely related least cisco (Coregonus sardinella Valenciennes 1848), which inhabits many North American and Siberian freshwaters, can successfully occupy estuary waters of varying salinities up to 32 PSU (Craig, 1984). The populations assigned to each of these two Coregonus species are not monophyletic and are so much alike that some researchers argue that they constitute just one species (Borovikova et al, 2013;Borovikova & Artamonova, 2021), further suggesting a high potential for significant population-specific local adaptations within the C. albula species complex (potentially including the Baltic Sea populations).…”
Section: Year-class Strengthmentioning
confidence: 99%
“…Divergence may involve only a few genes under selection, possibly clustered throughout the genome (genomic islands), with the rest of the genome remaining largely homogenous as a result of gene flow (Franchini et al, 2013;Jacobs et al, 2018;Nosil et al, 2021). Smith and Skúlason (1996) and Skúlason et al (1999) While in practice, it can be difficult to differentiate between allopatric and sympatric origins, allopatrically evolved lineages might be expected to have colonised multiple waters and populations sharing genetic ancestry could be found elsewhere (Mehner et al, 2021). On the other hand, populations that have evolved in sympatry should share greater genetic ancestry to each other than to similar populations that have evolved in parallel in other waters.…”
Section: Sympatric Originsmentioning
confidence: 99%
“…While in practice, it can be difficult to differentiate between allopatric and sympatric origins, allopatrically evolved lineages might be expected to have colonised multiple waters and populations sharing genetic ancestry could be found elsewhere (Mehner et al, 2021). On the other hand, populations that have evolved in sympatry should share greater genetic ancestry to each other than to similar populations that have evolved in parallel in other waters.…”
Section: Evolution Of Salmonid Sympatric Populationsmentioning
confidence: 99%